Main Character™s Conflict and Defense Mechanisms in The Novel œTentang Kamu by Tere Liye - Saragih, Lilia Sarah Indriani; Damanik, Sisila Fitriany; Setiasari, Winda (Universitas Negeri Medan, 2021)
The study dealed with the maincharacter™s conflicts and defensemechanisms found in a novel œTentangKamu written by Tere Liye. The objectivesof this study were to find out the types ofconflict of the main character and thedefense mechanism that is reflected insolving the problem. The sources of thedata were taken from the novel œTentangKamu By Tere Liye. This was anobservation study because this studyfocused on the analysis of spoken languagein the novel. The collected data wereidentified, divided, and analyzed based onliterature and psychology perspectives ofIslam™s (2016) theory and defensemechanisms by Cramer (2006). Thefindings show that Sri Ningsih, as the maincharacter, faces the external conflict whichis described as person vs nature whereasthe internal conflicts is person vs himselfwhich describes the features of sadness,anger, betrayal, anxiety, love and regret asexperienced by the main character. Theconflict between person vs. herself(internal conflict) becomes the mostcommon conflict faced by the maincharacter then it was followed with thedefense mechanism of denial andidentification.